Dosaje de radionucleidos en los complejos termales de la provincia de Entre Ríos, Argentina - De Michele, Daniel; Giacomino, Marta; Belderrain, Andrés; Canoba, Analia; Czerniczyniec, Mariela; Gnoni, Gabriela (Anales de Hidrología Médica, 2008)
Natural radionuclide (U, Pb 210 Ra 226 y Rn 222) activity concentrations were measured for first time in ten different geothermal spas of Entre Ríos, Argentina. Rn 222 concentration was between the limit detection and 6300 ± 1314 Bq/m3. Highest Rn 222 found level, was under the international standard required to define water as “radioactive” (67 Bq/l). Ra 226 concentration was between the limit detection and 0,097 ± 0,021 Bq/L. Pb 210 concentration was between the limit detection and 170 ± 34 mBq/. Uraniun concentration was between 1,2 ± 0,1 and 19,4 ± 1,9 mg/L. Except for Pb 210 in Federación Thermal Spa (170 mBq/l), we did not find any trace of radioactivity in Entre Rios thermal water.